Legal Protection for Micro-Entrepreneurs in Tax Disputes: A Comparative Study of Indonesia and Malaysia - Prihatin Effendi; Mashudi, Mashudi (Sean Institute, 2025)
This study explores the implementation of legal protection mechanisms for micro-entrepreneurs involved in tax disputes in Indonesia and Malaysia, using a qualitative comparative case study approach. By focusing on two core variables tax regulation compliance and access to legal aid and considering the moderating role of national legal contexts, the research examines institutional, procedural, and cultural differences that shape tax justice outcomes. Data were collected through in-depth interviews with micro-entrepreneurs, legal aid practitioners, and tax officials, complemented by secondary sources including legal documents and scholarly literature. The findings reveal significant disparities between the two countries: while Malaysia has institutionalized early-stage mediation and integrated legal aid into its tax dispute framework, Indonesia’s system remains reactive, fragmented, and inaccessible to most micro-entrepreneurs. These structural differences impact not only the effectiveness of dispute resolution but also taxpayer compliance and trust in legal institutions. The study highlights the importance of institutional synergy, legal awareness, and early legal intervention in promoting equitable access to tax justice. Practical recommendations include reforming Indonesia’s legal aid structure, enhancing inter-agency collaboration, and introducing non-litigious resolution mechanisms. This research contributes to regional discourse on fiscal justice and offers insights for policy reforms aimed at supporting vulnerable economic actors within developing legal systems.